2004
DOI: 10.14295/ras.v18i1.1339
|View full text |Cite
|
Sign up to set email alerts
|

Influência Do Depósito Sanitário Metropolitano De Belém (Aurá)

Abstract: RESUMO ABSTRACTSlingram Eletromagnetic Measurements were carried out in an area located between the Belem Solid Waste Deposit and Agua Preta Lake that supplies water for consumption in Belem. The objective of the work was to verify possible contamination of the lake by underground migration of leachate derived from the waste deposit. Electromagnetic measurements allowed to build images of the underground electrical conductivity distribution. The results show that detected conductivity changes are better explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…O crescente aumento de resíduos orgânicos produzido pelas atividades cotidianas da população pode resultar em graves riscos de contaminação aos recursos naturais e descaracterização de paisagem (PERAZZINI e BITTI, 2010). A preocupação acima evidenciada se refere ao chorume que é exposto como fator contaminante, resultante da decomposição dos resíduos orgânicos e sendo líquido, de cor escura, odor desagradável e altamente tóxico, que pode contaminar seriamente o subsolo (OLIVEIRA e JUCÁ, 1999) e as águas subterrâneas (BAHIA et al, 2004) com metais pesados e outras substâncias altamente prejudiciais à saúde humana. O Brasil é o 3º maior produtor de frutas tropicais in natura no mundo.…”
Section: Introductionunclassified
“…O crescente aumento de resíduos orgânicos produzido pelas atividades cotidianas da população pode resultar em graves riscos de contaminação aos recursos naturais e descaracterização de paisagem (PERAZZINI e BITTI, 2010). A preocupação acima evidenciada se refere ao chorume que é exposto como fator contaminante, resultante da decomposição dos resíduos orgânicos e sendo líquido, de cor escura, odor desagradável e altamente tóxico, que pode contaminar seriamente o subsolo (OLIVEIRA e JUCÁ, 1999) e as águas subterrâneas (BAHIA et al, 2004) com metais pesados e outras substâncias altamente prejudiciais à saúde humana. O Brasil é o 3º maior produtor de frutas tropicais in natura no mundo.…”
Section: Introductionunclassified
“…Similar to CO2aq, pCO2 showed a high CV (CV = 0.6), indicating strong variations across the studied period, indicating a low buffer capacity of the system, probably due to the anthropic impact adjacent to the lakes. Some studies have indicated that a sanitary landfill (Aurá dump) could be contributing through underground migration; however, a study by Bahia et al (2004) indicated that the variations in conductivity detected were better correlated with lithological variations than with leachate.…”
Section: Parameters Ph T (°C) Co2aqmentioning
confidence: 97%
“…Na Região Metropolitana de Belém-PA, diversos estudos relatam ocorrência de Fe em águas subterrâneas em concentrações superiores a 0,3 mg.L -1 , como é o caso das pesquisas de Bahia;Morales (2006), Carvalho et al, (2015), Freddo Filho (2018) e Vasconcelos Junior et al, (2018. Na região de Barcarena, Ferreira et al, (2018) e Pantoja et al, (2021) descreveram concentrações anômalas de Fe.…”
Section: Procedimentos Estatísticosunclassified